Evaluation of good practices in a pâtisserie in Recife/PE (Research, Society and Development, 2021)
Pâtisserie originated in France around the 16th century. Nowadays, it is widely used in the preparation of gourmet brigadeiros, gourmet sweets, cupcakes and pies. The aim of this study was to assess compliance with good practices, identify the main factors of food contamination and classify the establishment according to the percentage of adequacy. The following topics were analyzed during the months of May, June and July 2019, through the application of a checklist: the hygiene of the personal conduct of the handlers, receipt and storage of foodstuffs, hygiene during the preparation of food, facilities, equipment, pest control and procedures during distribution of the finished product. The establishment was classified according to the percentage of compliance determined in RDC 275/2002, which classifies into: Group 1 - 76 to 100% of items met, group 2 - 51 to 75% items met, group 3 - 0 to 50% service of items. Every month evaluated, a percentage of compliance above 80% was found, and in June the highest percentage of 87% was obtained. Therefore, it was classified in group 1 according to RDC 275/2002, totaling 78% of conformity, a favorable result to guarantee customers confidence in the purchase of products made in this Pâtisserie.